Effectiveness of Muscle Energy Technique Versus Conventional Therapy on Hamstring Tightness Among Sportspersons: A Comparative Study - Ashish Kumar; Jahanvi Dave (International Journal of Orthopedic Nursing and Practices, 2025)
Background: Hamstring tightness is a frequent musculoskeletal concern among athletes, often contributing to limited flexibility, decreased performance levels, and a higher likelihood of sustaining injuries. Muscle energy technique (MET) has gained attention as a therapeutic approach aimed at enhancing muscle length and improving overall function. Objective: This study aims to evaluate and compare the effectiveness of the MET with that of traditional physiotherapy methods in alleviating hamstring tightness in sportspersons. Methods: A total of thirty individuals between 18 and 40 years of age who were presented with hamstring tightness were selected using random sampling at the Maharishi Markandeshwar Institute of Physiotherapy and Rehabilitation, Mullana, Haryana. Participants were randomly assigned to two groups: Group A received MET intervention, while Group B was treated with conventional physiotherapy, including static stretching and cryotherapy. The intervention lasted for 15 days. Outcome measures included the Active Knee Extension (AKE) Test and the Back-Saver Sit and Reach (BSSR) Test, recorded pre- and post-intervention. Data was analyzed using SPSS (version 21.0) with the Wilcoxon signed-rank test. Results: Both MET and conventional therapy groups showed statistically significant improvements in AKE and BSSR scores (p = 0.001). The MET group demonstrated slightly greater mean improvement in flexibility compared to conventional therapy. Conclusion: MET and conventional therapy are effective in reducing hamstring tightness; however, MET provides a more efficient and quicker improvement in muscle flexibility among sportspersons.
Keywords: Flexibility; Sportspersons; conventional therapy; hamstring tightness; muscle energy technique; physiotherapy